2019
DOI: 10.3390/v11121158
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Interaction Network Used by Potyviruses in Virus–Host Interactions at the Protein Level

Abstract: Host proteins that are central to infection of potyviruses (genus Potyvirus; family Potyviridae) include the eukaryotic translation initiation factors eIF4E and eIF(iso)4E. The potyviral genome-linked protein (VPg) and the helper component proteinase (HCpro) interact with each other and with eIF4E and eIF(iso)4E and proteins are involved in the same functions during viral infection. VPg interacts with eIF4E/eIF(iso)4E via the 7-methylguanosine cap-binding region, whereas HCpro interacts with eIF4E/eIF(iso)4E v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 87 publications
(194 reference statements)
1
23
0
Order By: Relevance
“…However, the exact nature of the molecular functions of the VPg-eIF4E interaction in potyvirus infection has remained elusive. In this study, we approached the functions of the VPg-eIF(iso)4E interaction in PVA infection by dissecting the infection process with the mutated PVA VPgmut that carried similar mutations in the conserved eIF4E binding site YXXXXLΦ in PVA VPg as in [43,45]. In [45], the authors demonstrated that this binding site contributes to the capacity of PVA VPg to bind eIF(iso)4E and reported that it is crucial for the infectivity of PVA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the exact nature of the molecular functions of the VPg-eIF4E interaction in potyvirus infection has remained elusive. In this study, we approached the functions of the VPg-eIF(iso)4E interaction in PVA infection by dissecting the infection process with the mutated PVA VPgmut that carried similar mutations in the conserved eIF4E binding site YXXXXLΦ in PVA VPg as in [43,45]. In [45], the authors demonstrated that this binding site contributes to the capacity of PVA VPg to bind eIF(iso)4E and reported that it is crucial for the infectivity of PVA.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the PG-like aggregates contained, in addition to the P0 protein, a substantial amount of eIF(iso)4E in VPg mut -expressing cells. An interesting network of binding sites was demonstrated in [45], in which PVA VPg binds to HCPro and to two binding sites in eIF4E/(iso)4E, one of which is shared with HCPro (the binding domain for proteins that carry the YXXXXLΦ motif). The abundant presence of eIF(iso)4E in PGs in spite of VPg mut may arise from the interaction of eIF(iso)4E with HCPro [43,45].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations